Fluid Branding: Die Kunst der beständigen Veränderung. Genügt das Konzept des Fluid Branding den Anforderungen für den Aufbau starker Marken? - Lisa M. Hasenmaile; Florian Botzenhardt; Hans-Michael Ferdinand (Markenbrand, 2016)
– For a long time-period, continuity has been one of the most important rules for successful brand management. Contrariwise, modern media such as the internet and apps have accelerated marketing and brand management to a scenario that requires real-time-interactions with customers, competitors and the community. In this fast paced-environment, brands like Google have implemented Fluid Branding. The appearance of a logo or the packaging can now be modified and communicated within an extremely short amount of time. This article evaluates if the concept of Fluid Branding can be used for the development and management of strong brands that fulfill all tasks a brand traditionally must cover. Based on the magical branding triangle by Esch, the concept Fluid Branding is evaluated. It becomes apparent that Fluid Branding is able to develop and maintain strong brands despite breaking some long-proven rules. However, the concept needs a lot of attention and skill to still achieve the goals of brand management.
Keywords: 650